The Significance of Conceptual Metaphor in Belles-Lettres Texts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the significance of conceptual metaphors in belles-lettres, focusing on their cognitive, thematic, and emotional roles within literary texts. Drawing on the theory of conceptual metaphors, the paper examines how these metaphors shape the way readers understand abstract concepts, structure complex ideas, and experience emotions in literature. By analyzing examples from works such as Shakespeare, Kafka, Dickinson, and Woolf, the article demonstrates how conceptual metaphors provide a deeper cognitive and emotional engagement with themes like love, death, time, and identity. Additionally, it highlights the philosophical and cultural dimensions of metaphors, showing how they reflect and challenge societal values and ideologies. Ultimately, the article argues that conceptual metaphors are fundamental not only to the intellectual depth of literary works but also to their aesthetic appeal, contributing to the power of belles-lettres to shape both individual thought and collective consciousness.